2021
DOI: 10.1017/dmp.2021.262
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Predictors of Social Distancing Compliance in the United States during the COVID-19 Pandemic

Abstract: Objective: Through the application of the Health Belief Model, this study sought to explore how relationships between perceived susceptibility, severity, and benefits of social distancing recommendations, as well as psychological factors, may impact compliance with COVID-19 social distancing recommendations in the United States. Methods: Between October and November 2020, a convenience sample of English-speaking adults in the United States completed an online, cross-sectional survey whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Based on TPB the immediate predictors of the behavior are behavioral intention with constructs of attitude, subjective norm, and perceived behavioral control. 5 The TPB constructs (attitude, subjective norm, and perceived behavioral control) and behavioral intention were positively associated with hand washing practice, 19 , 63 , 64 social distance, 65 67 face mask-wearing, 64 , 68 71 social isolation, 72 , 73 and enhanced community quarantine. 74 This finding suggested that the TPB could be used to predict health preventive behavior; therefore, it is important to guide the development of effective healthy messages on COVID-19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Based on TPB the immediate predictors of the behavior are behavioral intention with constructs of attitude, subjective norm, and perceived behavioral control. 5 The TPB constructs (attitude, subjective norm, and perceived behavioral control) and behavioral intention were positively associated with hand washing practice, 19 , 63 , 64 social distance, 65 67 face mask-wearing, 64 , 68 71 social isolation, 72 , 73 and enhanced community quarantine. 74 This finding suggested that the TPB could be used to predict health preventive behavior; therefore, it is important to guide the development of effective healthy messages on COVID-19 preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…This current review of UK data together with the broader international literature have found that people's beliefs about the Covid-19 disease and about the TRBs themselves predict behaviour [32,36,[47][48][49]. Studies reported in this review show that the UK general public were motivated to change their behaviour because they wished to avoid the negative consequences of the Covid-19 disease on themselves, their family and friends and wider society and believed that the consequences of actually performing preventive and avoidant behaviours would be beneficial.…”
Section: Key Findingsmentioning
confidence: 88%
“…Pandemic public health measures (PPHM) play an important role in controlling the spread of Covid-19. Preliminary findings suggest that people who perceive Covid-19 as low risk are more likely to be non-adherent to PPHMs 1 . Literature in the severely mentally ill (SMI) is limited.…”
mentioning
confidence: 86%